INTERLEUKIN-1 RECEPTORS ANTAGONIST INTRACEREBRAL ADMINISTRATIONS ANTICONVULSIVE EFFICACY IN CONDITIONS OF KINDLING MODEL OF EPILEPTOGENESIS - Vastyanov, R.S.; Stoyanov, A.N.; Krepec, Yu.S.; Dzygal, A.F.; Beseda, Ya.V.; Puchkova, A.V. (World of Medicine and Biology, 2020)
The purpose of the work is to study the chronic convulsive activity intensity in conditions of picrotoxin-induced kindling and due to recombinant antagonist of interleukin-1 receptors introduction as well as registration of electrographic activity of brain structures and investigation of electrical potentials generated by subcortical structures in conditions of recombinant antagonist of interleukin-1 receptors administration. The experimental data are given showing the anticonvulsive action after recombinant antagonist of interleukin-1 receptors intraperitoneal, intracerebral administrations. Recombinant antagonist of interleukin-1 receptors intrahippocampal, intranigral and intracerebroventricular microinjections resulted in anticonvulsive efficacy expressed mainly by seizure intensity decreasing. The most pronounced anticonvulsive effects were obtained after recombinant antagonist of interleukin-1 receptors intracerebroventricular microinjection which additionally characterized by the first seizure reactions latency increase and the number of rats with tonic-clonic seizures decrease. Less expressed anticonvulsive efficacy was registered in case of recombinant antagonist of interleukin-1 receptors both intrahippocampal and intranigral administrations. The authors conclude about the principal possibility of the anticonvulsive efficacy realization after recombinant antagonist of interleukin-1 receptors intraperitoneal and intracerebral administrations in conditions of experimental chronic epileptogenesis.